Malignant melanoma: Round Table Malign melanoma; coordinator Julio C Priario - Priario, Julio C (Cirugía del Uruguay, 1974)
Malignant melanoma is initially a puzzling tumor, because all the parameters we have for diagnosis and treatment of malignant tumors usually do not fit into malignant melanoma.